Instructional Design: Multi-Site Study of the Integration of Islam in Science Teaching in Java, Indonesia - Abd Ghofur; Joel C. Kuipers; Askuri Askuri (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2021)
This study aims to describe the baseline of instructional strategies currently deployed by teachers in the form of goal setting, media selection, application of methods, and evaluation of learning in relation to Islamic values ​​in science teaching. This research was designed in the form of a qualitative description by involving 18 Islamic schools spread over three regions in Indonesia, namely Malang, Lamongan, and Yogyakarta. Methods of data collection used observation forms, ethnographic video during the learning process, interviews with education stakeholders, Forum Group Discussion (FGD) with students, and documentation study for 6 months. Although Islamic schools in the selected study areas in Java, Indonesia have embraced the integration of Islam into science teaching, as mentioned in the Core Competencies [KI] in the National Curriculum 2013), however, the implementation of it is still not optimal. In addition, the integration of Islam in science teaching is mostly done by teachers through lecture methods. While most teachers expressed interest in the integration of Islam and science, many teachers expressed anxiety about their competence in addressing complex theological issues. The majority of science teachers in Islamic schools have similar strategies in developing ways to integrate the science curriculum. One key strategy is to browse online and find verses from the Qur'an that seem relevant to the lesson.